Application of fuzzy mathematic evaluation in the optimization of stewed pork processing - GU Wei-gang; PENG Yan; ZHANG Jin-jie; YAO Yan-jia; JI Rong; CHEN Jian-chu (浙江大学学报. 农业与生命科学版, 2011)
Fuzzy mathematic evaluation model was introduced to optimize the process of stewed pork. As five key factors, colour, texture and mouthfeel of the stewed pork, taste and odour of the soup were on weight analysis based on sensory evaluation, and the integrated assessment system was established. On this basis, different ratios of material to water, stewed temperatures and time were optimized by the method of fuzzy mathematic evaluation. The results showed that the optimum stewed conditions were as follows: the pork to water ratio of 1∶1.5, stewed temperature of 70℃ and stewed time of 2 h. Sensory evaluation combined with fuzzy mathematics make the estimation more scientific, reasonable and objective, which will have broad application perspectives in the field of food processing.